2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--18038
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Teaching Assistants' Decision Making and Perceptions of Autonomy

Abstract: Graduate students are increasingly being called upon to teach engineering courses, yet little is known about their experiences. Based in self-determination theory, the purposes of this study were to investigate how autonomous graduate teaching assistants (GTAs) feel in their teaching duties and how graduate teaching assistants" descriptions of their teaching decisions relate to their perceptions of autonomy. Six doctoral students from five departments at a large, land-grant research university were recruited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The graduate students with TA experience prior to being an instructor of record reported less autonomy in teaching as compared to their peers who had only taught as instructors of record. This finding aligns with results from a small-scale study involving graduate students employed as TAs of undergraduate engineering courses, where the majority reported a lack of autonomy in making teaching decisions (Winters and Matusovich, 2011). In a study of graduate student TAs of an introductory science course, Dotger (2011) reported that conversations between TAs focused mostly on logistics and managing problems with students, rather than on student learning or pedagogy.…”
Section: How Do Professional Development Ta Experience and Academic D...supporting
confidence: 79%
“…The graduate students with TA experience prior to being an instructor of record reported less autonomy in teaching as compared to their peers who had only taught as instructors of record. This finding aligns with results from a small-scale study involving graduate students employed as TAs of undergraduate engineering courses, where the majority reported a lack of autonomy in making teaching decisions (Winters and Matusovich, 2011). In a study of graduate student TAs of an introductory science course, Dotger (2011) reported that conversations between TAs focused mostly on logistics and managing problems with students, rather than on student learning or pedagogy.…”
Section: How Do Professional Development Ta Experience and Academic D...supporting
confidence: 79%
“…While several studies highlight the importance of pedagogical autonomy when supporting student development as educators (Kajfez and Matusovich, 2017; Gilmore, 2010; Winters and Matusovich, 2011; McDaniels, 2010), this study complements existing work (Goller and Harteis, 2014; Emmioglu et al , 2017; Benbow et al , 2011) emphasizing instances of professional autonomy being used to increase a students’ viability in the academic job market, to support their overall preparation for an academic career, and/or to allow them to develop the necessary skills for a career that is focused mainly on teaching, as opposed to research. The findings presented here also portray doctoral students as agents of their own learning, with heavy reliance on self, within a graduate curriculum (Goller and Harteis, 2014; McDaniels, 2010).…”
Section: Discussionmentioning
confidence: 99%